Acute Lymphoblastic Leukemia in Combined Methylmalonic Acidemia and Homocysteinemia (cblC Type): A Case Report and Literature Review - Zhu, Jun; Wan, Shuisen; Zhao, Xueqi; Zhu, Binlu; Lv, Yuan; Jiang, Hongkun (Frontiers in Genetics, 2022)
Background: Methylmalonic acidemia (MMA) can display many clinical manifestations, among which acute lymphoblastic leukemia (ALL) has not been reported, and congenital heart disease (CHD) is also rare. Case presentation: We report an MMA case with ALL and CHD in a 5.5-year-old girl. With developmental delay and local brain atrophy in MRI, she was diagnosed with cerebral palsy at 9 months old. Rehabilitation was performed since then. This time she was admitted to hospital because of weakness and widespread bleeding spots. ALL-L2 (pre-B-cell) was confirmed by bone marrow morphology and immunophenotyping. Echocardiography showed patent foramen ovale. The girl was treated with VDLD and CAML chemotherapy, during which she developed seizures, edema and renal insufficiency. Decrease of muscle strength was also found in physical examination. Screening for inherited metabolic disorders showed significantly elevated levels of methylmalonate-2, acetylcarnitine (C2), propionylcarnitine (C3), C3/C2 and homocysteine. Gene analysis revealed a compound heterozygous mutaion in MMACHC (NM_015560): c.80A＞G (p.Gln27Arg) and c.609G＞A (p.Trp203*). CblC type MMA was diagnosed. Intramuscular injection of cyanocobalamin and intravenous L-carnitine treatment were applied. The edema vanished gradually, and chemotherapy of small dosage of vindesine was given intermittently when condition permitted. 2 months later, muscle strength of both lower limbs were significantly improved to nearly grade 5. The levels of methylmalonic acid and homocysteine were improved. Conclusion: Metabolic disease screening and gene analysis are very necessary for diseases with complex clinical symptoms. ALL can be a rare manifestation for MMA.